THE INFLUENCE OF HUMOR ON TV SHOW TOWARDS BRAND AWARENESS (Case Study Opera Van Java) - Sumigar, Christy A.; Tasik, Hizkia H.D. (Universitas Sam Ratulangi, 2019)
Abstract: The rapid developments of technology forces people who are working in every industry to adjust themselves of the technology growth, especially for those who are working in broadcasting industry. The existence of online platforms which allow people to access various online videos finally makes broadcast industry players improve the quality of their TV programs. Hence, they may compete with online media. One type of TV programs which became the favorite of many people was a TV shows wrapped with humor. The purpose of this study is to analyze the influence of humor on TV show towards brand awareness. The case study in this research is Opera Van Java. This study uses primary data which is obtained through questionnaires and analyzed using multiple linear regressions. The population is Opera Van Java audience in Manado, with 209 respondents as the sample. The study shows that happiness, content, and message delivery have significant influences towards the brand awareness. Although Opera Van Java is one of the most successful TV show, they still have to maintain the originality of their content, maintain their creativities in creating good quality content to entertain the audiences, and Â pay more attention about how they deliver the messages.Keywords: brand awareness, happiness, content, message delivery